Design and manufacture simple portable astro receiver stand - Abdul Aziz, Safiee (2010)
This thesis deals with design and fabricate simple portable Astro receiver stand. Most Astro transmitter stand stationary and difficult to remove and not portable User or the people of Malaysia do not have to worry about to move or carry anywhere, Since Simple Portable Astro Receiver Stand (SPARS) is produced whereas the stand is not heavy and easy for storage. Because SPARS is lightweight and not too big, the installation does not revere long time, for example in the corridor, with clamp that has been modified, easier to be installed anywhere. This product can be installed or adjusted at high or lower place. Final product is durable and can withstand cold and rough environment. It is able to withstand tropical climates and can be placed anywhere, inside or outside the hause.